'Di sebalik tabir' sejarah politik Malaysia 1945-1957 - Azmi Arifin; Abdul Rahman Haji Ismail (Penerbit Universiti Sains Malaysia, 2016)
Political history of Malaysia, 1945-1957; collection of articles